2002
DOI: 10.1093/ajcn/76.6.1191
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial role of dietary phytoestrogens in obesity and diabetes

Abstract: Evidence is emerging that dietary phytoestrogens play a beneficial role in obesity and diabetes. Nutritional intervention studies performed in animals and humans suggest that the ingestion of soy protein associated with isoflavones and flaxseed rich in lignans improves glucose control and insulin resistance. In animal models of obesity and diabetes, soy protein has been shown to reduce serum insulin and insulin resistance. In studies of human subjects with or without diabetes, soy protein also appears to moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
383
2
20

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 573 publications
(415 citation statements)
references
References 100 publications
10
383
2
20
Order By: Relevance
“…Several studies have also reported that soy protein rich in isoflavones reduces fat-pad mass in rats, accompanied by decreased serum TG concentrations and cholesterol levels (Akahoshi et al, 2004;Torres et al, 2006). It has been suggested that isoflavones are the principal physiologically active components responsible for the lipid-lowering effects of soy (Bhathena and Velasquez, 2002). The results of the present study showed that serum TG concentrations in broilers decreased following in ovo Eq injection during the early embryonic period, without changes in BW or fat deposition.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Several studies have also reported that soy protein rich in isoflavones reduces fat-pad mass in rats, accompanied by decreased serum TG concentrations and cholesterol levels (Akahoshi et al, 2004;Torres et al, 2006). It has been suggested that isoflavones are the principal physiologically active components responsible for the lipid-lowering effects of soy (Bhathena and Velasquez, 2002). The results of the present study showed that serum TG concentrations in broilers decreased following in ovo Eq injection during the early embryonic period, without changes in BW or fat deposition.…”
Section: Discussionsupporting
confidence: 65%
“…Numerous studies have demonstrated that isoflavones have beneficial effects on lowering serum lipids and decreasing body fat deposition (Bhathena and Velasquez, 2002). Cederroth et al (2007) reported that male CD-1 mice fed from conception to adulthood a high soy-containing diet significantly increased energy expenditure and decreased adiposity (Cederroth et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have associated phytoestrogen consumption and/or excretion with reduced risk for hormone-dependent cancers, as well as for coronary heart disease, symptoms of menopause and osteoporosis (Adlercreutz et al, 1992;Adlercreutz 1995;Gambacciani et al, 1997;Anderson et al, 1999;Cassidy and Griffin, 1999;Adlercreutz 2002;Bhathena and Velasquez, 2002;Clarkson, 2002;de Kleijn et al, 2002). For example, soy ingestion in rodents has been associated with a decrease in the growth of breast cancer tumors (Barnes et al, 1990), and flaxseed ingestion protects against both breast and colon cancers in rodents Thompson, 1991, 1992).…”
Section: Introductionmentioning
confidence: 99%